Technological Pedagogical and Content Knowledge (TPACK) Based Language Immersion as a New Trend in Arabic Language Learning at Indonesian Pesantren - Jauhar Ali; Tulus Musthofa; Nurhadi Nurhadi (ALSINATUNA, 2025)
The rapid development of information technology demands adjustments to established pedagogical models, particularly in language acquisition environments such as Islamic boarding schools (pesantren). This study aims to investigate the implementation model and efficacy of the Technological Pedagogical and Content Knowledge framework in enhancing the culture of active, 24-hour Arabic language immersion that characterises Islamic boarding schools (pesantren) in Indonesia. This study uses a qualitative case study design, collecting extensive data through semi-structured interviews with teachers and students based on the TPACK construct, non-participant observation of formal instructional activities and informal digital use by students and non-teaching students, and analysis of curriculum documents. The findings confirm that although teachers' competencies in traditional Content Knowledge (CK) and Pedagogical Knowledge (PK) are high, effective technology integration (Technological Pedagogical Knowledge, TPK) remains inconsistent, often limited to introductory presentation tools. However, successful TPACK applications are identified when technologies such as authentic video platforms (e.g., istimā’ or kalām learning utilising Al Jazeera channels) and narrative creation applications are strategically employed to facilitate functional communication, ensuring contextual expansion of L2 use beyond the formal classroom. In conclusion, the implementation of TPACK aligns traditional language learning methods with modern technology, thereby significantly increasing students’ engagement and productive Arabic language skills.